2022
DOI: 10.1029/2021ef002360
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in China: Will Decoupling of Their Emissions and Socioeconomic Growth Emerge?

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are hydrophobic organic pollutants with semivolatile, persistent, and carcinogenic properties. The United States Environmental Protection Agency (USEPA) has identified 16 PAHs as priority pollutants (Keith & Telliard, 1979). The widespread occurrences of PAHs in air, surface water, soils, sediments, and biota (Han and Currell, 2017;Lang et al., 2008;Zhang & Chen, 2017) have been a concern because of their toxic effects on ecosystem and human health. In fact, they are tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…The percentage contributions of biofuels and waste to the total PES have decreased while those of solar, wind, hydro power, nuclear, and natural gas have increased over the last two decades in both countries (Figure 2). Recently, the coupling between emissions of polycyclic aromatic hydrocarbons (PAHs) driven by energy transitions and socioeconomic factors over China was examined, and the results showed that after 2016 the PAHs emissions were decoupled from socioeconomic growth (Cao et al, 2022). It was predicted that emissions of PAHs will reach a peak in 2035 when driven only by energy transition under the shared socioeconomic pathways (Cao et al, 2022).…”
Section: Energy Transitions Over Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage contributions of biofuels and waste to the total PES have decreased while those of solar, wind, hydro power, nuclear, and natural gas have increased over the last two decades in both countries (Figure 2). Recently, the coupling between emissions of polycyclic aromatic hydrocarbons (PAHs) driven by energy transitions and socioeconomic factors over China was examined, and the results showed that after 2016 the PAHs emissions were decoupled from socioeconomic growth (Cao et al, 2022). It was predicted that emissions of PAHs will reach a peak in 2035 when driven only by energy transition under the shared socioeconomic pathways (Cao et al, 2022).…”
Section: Energy Transitions Over Asiamentioning
confidence: 99%
“…Recently, the coupling between emissions of polycyclic aromatic hydrocarbons (PAHs) driven by energy transitions and socioeconomic factors over China was examined, and the results showed that after 2016 the PAHs emissions were decoupled from socioeconomic growth (Cao et al, 2022). It was predicted that emissions of PAHs will reach a peak in 2035 when driven only by energy transition under the shared socioeconomic pathways (Cao et al, 2022). Typically, the energy growth, GDP growth, and CO 2 emissions are tightly coupled; however, the coupling/de-coupling between energy, GDP, and emissions of climate-forcing air pollutants (e.g., BC) and the resultant atmospheric effects over Asia are unclear and have not been properly investigated yet.…”
Section: Energy Transitions Over Asiamentioning
confidence: 99%
“…Within China, measures are being taken to convert the domestic coal used for heating and cooking to natural gas, and renewable energy is being used extensively. In addition, according to Cao et al, PAH emissions from 2016 to 2020 from domestic coal across China have been nearly halved [25]. Thus, considering also the results of the back trajectory analysis, one of the main reasons for the markedly downward behavior in winter values is thought to be the decrease in the amount of biomass and coal burned for heating and other operations in cold continental regions such as northern China.…”
Section: Behaviors In Pah Concentrations and Their Causesmentioning
confidence: 99%
“…In 2021, community-acquired infections still occurred frequently in China, and factory operations were suspended each time. As a result, the concentration of PAHs emitted in China decreased, which is presumed to have affected the overall decrease in the concentration of PAHs in Nagasaki in 2020 and 2021. across China have been nearly halved [25]. Thus, considering also the results of the back trajectory analysis, one of the main reasons for the markedly downward behavior in winter values is thought to be the decrease in the amount of biomass and coal burned for heating and other operations in cold continental regions such as northern China.…”
Section: Behaviors In Pah Concentrations and Their Causesmentioning
confidence: 99%
“…Nonetheless, a variety of research on trophic transfer and PAHs biomagnification indicate that PAHs may biomagnify in the aquatic food web and may eventually have harmful impacts on human health [33]. Several other studies also suggest the carcinogenic and non-carcinogenic risks of PAHs in aquatic ecosystems, and the risk studies are the major concern of PAHs research [34][35][36]. Moreover, PAHs are also bound to atmospheric fine particles, causing serious health effects.…”
Section: Introductionmentioning
confidence: 99%